1998
DOI: 10.1128/jvi.72.6.5067-5075.1998
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 Latency-Associated Transcripts Suppress Viral Replication and Reduce Immediate-Early Gene mRNA Levels in a Neuronal Cell Line

Abstract: During herpes simplex virus type 1 (HSV-1) latent infection in human dorsal root ganglia, limited viral transcription, which has been linked to HSV-1 reactivation ability, takes place. To study the involvement of this transcription in HSV-1 replication in neuronal cells and consequently in viral latency, we constructed stably transfected neuronal cell lines containing (i) the entire HSV-1 latency transcriptionally active DNA fragment, (ii) the same DNA sequence with deletions of the latency-associated transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 73 publications
3
32
0
Order By: Relevance
“…One may speculate that the neurons with low levels of LAT express higher levels of IE genes. This hypothesis is in accordance with HSV‐1 in vitro experiments that clearly demonstrated that LAT can reduce the steady‐state mRNA levels of ICP0, ICP4 and ICP27 (26).…”
Section: Discussionsupporting
confidence: 87%
“…One may speculate that the neurons with low levels of LAT express higher levels of IE genes. This hypothesis is in accordance with HSV‐1 in vitro experiments that clearly demonstrated that LAT can reduce the steady‐state mRNA levels of ICP0, ICP4 and ICP27 (26).…”
Section: Discussionsupporting
confidence: 87%
“…Because ICP0 is still intact in the LAT null virus dLAT2903 used in this study, the effects seen in this study are not due to lack of ICP0 expression. However, LAT may repress expression of ICP0 during latency (58), although conflicting evidence has also been reported (59). Therefore, it is possible that continued expression of ICP0 in the absence of the LAT could contribute to downregulation of JAK-1 and JAK-2.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that a LAT‐negative mutant could be at a greater propensity of spontaneous reactivation within murine TG, especially given the increased levels of TK mRNA, an early transcript dependent on the presence of ICP4 for expression (Chen et al ., ). Subsequently, the production of mouse neuronal cell lines expressing various forms of the LAT locus continued to provide evidence that LAT could exert a repressive effect on IE mRNA levels (Mador et al ., ). In the same study, the authors demonstrated that productive HSV replication was reduced in cell lines encoding the LAT locus during low multiplicity infection, but not in cell lines with a deletion in the promoter driving LAT transcription.…”
Section: Virus Transcription During Latencymentioning
confidence: 97%